Asparaginase-associated hyperammonemia - Raheel Altaf Raja; Bodil Als-Nielsen; Allan M. Lund; Hendrik Vilstrup; Kim Peder Dalhoff; Kjeld Schmiegelow (Haematologica)
Asparaginase is an essential drug in the treatment of acute lymphoblastic leukemia, and discontinuation of asparaginase therapy due to clinical toxicity or silent inactivation may lead to reduced event-free survival. Common toxicities include hypersensitivity reactions, acute pancreatitis, thrombosis, hepatotoxicity, and hyperlipidemia. In addition, several small case series have described asparaginase-associated hyperammonemia (AAH), the true frequency and clinical importance of which, both short-and long term, remains unclear. Descriptions vary from asymptomatic patients to those with severe, acute encephalopathy leading to withdrawal of asparaginase therapy. The cause and management of the problem remains elusive. This review summarizes current knowledge on AAH, including its pathogenesis, clinical presentation, and possible interventions.